Perbandingan Basis Salep Terhadap Aktivitas Antibakteri Ekstrak Kasar Bromelin Dari Bonggol Nanas: Comparison of Hydrocarbon Ointment Bases and Absorption on the Antibacterial Activity of Bromelin Crude Extract from Pineapple Tuber - Barmi Hartesi; Desi Sagita; Helsa Raudatul Qalbi (Jurnal Farmasi Galenika (Galenika Journal of Pharmacy) (e-Journal), 2020)
The pineapple tuber contains bromelain enzyme which is able to inhibit the growth of Staphylococcus aureus and Pseudomonas aeruginosa causing skin infections. The topical preparation that good for treating skin infections is ointments. Ointments have two type of bases such as hydrocarbon and absorption base. This study aims to compare the comparison of ointment bases having antibacterial activity of Staphylococcus aureus and Pseudomonas aeruginosa. This research used experimental methods. The bromelain enzyme was extracted and purified with ammonium sulfate and then dialyzed. The bromelain enzyme with a concentration of 4% was formulated into ointment preparation with a base of hydrocarbons (F1, F2) and absorption base (F3, F4). Each formula was evaluated for organoleptic, homogenity, pH, spreadability, irritation test, stability and antibacterial activity. The results showed that all formulas with hydrocarbon base and absorbent base types met good topical preparation requirements, that are semi-solid, homogeneous, having a pH range of 4.5 - 6.5, stable during storage and not irritating on the skin. However, ointments based on hydrocarbons have the best antibacterial activity when compared to absorption base ointments. Formula 2 with a base of hydrocarbons have strong antibacterial activity against Staphylococcus aureus and Pseudomonas aeruginosa which is the best among the other formulas.